Predicting Candida Infection in Pediatric Intensive Care Unit using Candida Score in a Low-Resource Setting - Dicky Ari Risandy MD; Desy Rusmawatiningtyas MD; Firdian Makrufardi MD; Elisabeth Siti Herini MD, PhD; Nurnaningsih MD (SAGE Publishing, 2021)
Candida infection was previously thought to be rare in intensive care. With the increased use of broad-spectrum antibiotics, the incidence of candida infection increased significantly. Case-control study was done in patients ≤18 years of age treated for 3 days or more in Pediatric Intensive Care Unit (PICU) Dr. Sardjito General Hospital, Yogyakarta from January 2014 to December 2016. Overall, 43 children were included in this study as a case group with positive candida culture and 43 children as a control group with no candida culture. Cut off point of candida score is ≥3 from our subjects. The area under curve (AUC) value for cut off ≥3 was moderate (0,72). Candida score ≥3 has an odd ratio (OR) 6.8 (95% CI 2.4-18.6) with P  < .05. All of confounding factors in candida infection have no association with P  > .05. Candida score can be used as predictor of candida infection in PICU.